Utilization Of Gemini Ai In Developing Teaching Tools For Teacher Work Efficiency At SD Inpres Kumelembuay - Marsel Mamahit; Widdy H. F. Rorimpandey; Richard D. H. Pangkey (Literasi: Jurnal Pendidikan Guru Indonesia, 2026)
This study aims to describe the use of Gemini AI, the obstacles encountered, and solutions to these obstacles in developing teaching materials for teacher work efficiency at SD Inpres Kumelembuay. The method used is descriptive qualitative research. Data were collected through observation, interviews, and documentation involving class teachers of phases A, B, and C, physical education teachers, English teachers, the principal, and students. Data analysis techniques include data reduction, data presentation, and conclusion drawing. Data validity was tested by data triangulation. The results of the study indicate that the use of Gemini AI in developing teaching materials improves teacher work efficiency by simplifying the preparation of teaching materials, reducing administrative burdens, saving time, and being easy to use in accordance with current developments. However, there are obstacles such as unstable internet connections, difficulties in creating AI prompts/instructions/commands, device limitations, and a tendency to rely on AI without critical thinking. The proposed solutions include compiling teaching tools that will be used for several meetings at once when the internet network is stable, practicing creating AI prompts/instructions/commands more often from various sources, maximizing the available tools, and being critical in checking and re-editing the results of teaching tools compiled through Gemini AI.